2014
DOI: 10.1155/2014/406816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Modified Simiao Decoction on IL‐1β and TNFα Secretion in Monocytic THP‐1 Cells with Monosodium Urate Crystals‐Induced Inflammation

Abstract: Simiao pill, a Chinese herbal formula containing four herbs, has been used in the treatment of gouty arthritis for many years. The aim of this study was to explore the effects of modified Simiao decoction (MSD) on IL-1β and TNFα secretion in monocytic THP-1 cells with monosodium urate (MSU) crystals-induced inflammation. The MSU crystals-induced inflammation model in THP-1 cells was successfully established by the stimulation of phorbol 12-myristate 13-acetate (PMA) and MSU crystals. Then, the MSD-derived seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…As a classic formula derived from EM, SM is commonly used to treat gout and hyperuricemia in clinical (Hu et al, 2010;Hua et al, 2012), eliminating dampness, clearing heat and promoting blood circulation in terms of TCM through targeting UA synthetase, transporters and inflammatory cytokines. Literatures also suggest that SM could suppress inflammation and inhibit the release of IL-1β, TNF-α Liu et al, 2014). Besides, it could also significantly inhibit XOD activities in serum and liver, and reverse oxonate-induced alterations in renal URAT1, GLUT9, OAT1 mRNA and protein levels, resulting in the enhancement of renal urate excretion (Hua et al, 2012), which are consistent with those predicted from the gouty network.…”
Section: Discussionsupporting
confidence: 82%
“…As a classic formula derived from EM, SM is commonly used to treat gout and hyperuricemia in clinical (Hu et al, 2010;Hua et al, 2012), eliminating dampness, clearing heat and promoting blood circulation in terms of TCM through targeting UA synthetase, transporters and inflammatory cytokines. Literatures also suggest that SM could suppress inflammation and inhibit the release of IL-1β, TNF-α Liu et al, 2014). Besides, it could also significantly inhibit XOD activities in serum and liver, and reverse oxonate-induced alterations in renal URAT1, GLUT9, OAT1 mRNA and protein levels, resulting in the enhancement of renal urate excretion (Hua et al, 2012), which are consistent with those predicted from the gouty network.…”
Section: Discussionsupporting
confidence: 82%
“…However, MSU crystals-induced inflammation model in monocytes was rarely reported [ 5 ]. In our previous study, the MSU crystals-induced inflammation model in THP-1 cells was successfully established by the stimulation of PMA and MSU [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among effective prescriptions, Simiao pill, which is derived from Ermiao powder and described in a famous traditional Chinese medicine monograph Chengfang Biandu in Qing Dynasty of China, has been wildly employed for treatment of gout and inflammatory arthritis [ 8 ]. Our previous study also demonstrated that modified Simiao decoction significantly decreased IL-1 β release in THP-1 cells with MSU crystals-induced inflammation [ 9 ]. The ingredients of modified Simiao decoction are complicated, including alkaloids, flavones, and organic acids.…”
Section: Introductionmentioning
confidence: 99%
“…NOS is a catalytic enzyme which synthesizes NO, and NO is known to have a wide range of important physiological and pathological functions. NO has an important regulatory role in the cardiovascular, immune, nervous and digestive systems (35). Due to the reactivity and short half-life of NO, numerous studies have focused on NOS.…”
Section: Discussionmentioning
confidence: 99%